Is Telbivudine-Induced Polyneuropathy/Myopathy Reversible in Liver Transplant Recipients? - Turan, Ilker; Yapali, Suna; Gunsar, Fulya; Zeytunlu, Murat; Ersoz, Galip; Akarca, Ulus S.; Karasu, Zeki (WILEY, 2017)
68th Annual Meeting of the American-Association-for-the-Study-of-Liver-Diseases (AASLD) / Liver Meeting, Washington, DC, OCT 20-24, 2017